Modern aspects of the e-learning usage in the field of physical culture - Andriy Marakushyn; Oleksandr Piddubnyi; Artem Cherednichenko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: actualize the introduction of e-learning to motivate students to engage in movement activity. Material & Methods: method of generalization and analysis are selected, which was used to study the approaches, definitions and results of the study among different authors on the research topic. Results: generalized and analyzed: approaches to the formation of motivation in students for movement activity; definition of e-learning; results of the introduction of e-learning in the educational process of students from different authors. Conclusion: it is proved that the approaches of different authors on motivating students to movement activity do not include the use of modern e-learning tools; it is established that e-learning can be an excellent complement to the full-time form of education; directions for further scientific research are updated.